Paradise BookCafe / Adly Shukrie Yunus... [et al.] - Idam, Ninah Noor Zurimah; Wagimin, Nur Anisah; Tirinsinu, Siti Chanel; Marimbot, Fenizalin; Yunus, Adly Shukrie (2014)
Paradise BookCafe is combination of library and cafe or to be clear it is a combination of service which is serving customers with books and foods. The main purpose of Paradise BookCafe is to serve people in casualties. It is because, in library itself we cannot eat inside. If we hungry or has the urge to eat in time we are doing some revision or whatever in the library, we have to go out to the nearby cafe or restaurant to fill our empty stomach. But when we have cafe and library in the same place, we can save our precious time finding another nearby restaurant. Moreover, some people don't like the rules of library where we can't eat nor making some noises. In our cafe, we also provide Wifi so that our customer can access internet searching information that they need. The specialty goes to student who has assignment that require them to access internet in order to finish their work. Library is similar to archive, where the function is storage of information. Library enables people to discover a lot of things that helps to increase the knowledge and brain capacity. Meanwhile, cafe is a place where people will fill their empty stomach in order to maintain energy. Paradise Bookcafe not producing any new products or any new recipes. It is service. We also buy and sell books, magazines and many types of books. We also looking forward a contribution from public, any old books and newspaper that a mean to dispose. Any feedback from our customer is welcome in order to improve the quality of our service.